The impact on underground ventilation of the reduction of diesel emissions toxicity by water-in-oil fuel emulsification - E. D. Dainty; J. P. Mogan; A. Lawson (Canadian Institute of Mining, Metallurgy and Petroleum, 1981)
"The toxicity reduction of emissions from two diesel engines by the emulsification of water into fuel oil was investigated to determine the applicability of such systems to underground mining machinery. . The engines studied were: 1) the Deut; F6L7J4, four-stroke, air-cooled, 6-cylinder, V-configuration, indirect-injection (IDl) engine, and 2) the Detroit Deisel Allison Division 8V7JN, two-stroke, water-cooled, 8-cylinder, V-configuration, direct-injection (Dl) engine.The application of emulsified fuel treatment to the two-stroke engine did not prove to be practicable. In the case of the Deutz engine, however, substantial benefit resulted. For a modest J5 per cent water content in the fuel and an injection timing of24° BTDC, approximate reductions of40 per cent in the concentrations of both particulate matter and nitric oxide (NO) were produced. These reductions were accompanied by insignificant changes in other toxic constituents. The net result was an approximate 30 per cent reduction in the over-all exhaust toxicity for typical LHD operation as assessed by the Health Effects Index criterion. This toxicity reduction represents a significant advance from the points of view of an improved underground environment and/or reduced ventilation costs."